Effect of Light-Curing Unit Type and Bulk-Fill Composite Resins with Different Photoinitiators on Marginal Gaps of Class II Restorations - Fereshteh Naser Alavi; Farideh Darabi; Ashkan Salari; Arefeh Dehghan (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the effect of two types of light-curing units (second and third generations) and two types of bulk-fill composite resins with different photoinitiators - Tetric N-Ceram Bulk Fill (TNCB) and X-tra Fil (XTF) on gap formation at the gingival margins of Cl II restorations. Material and Methods: Fifty-six standard Cl II cavities were prepared on the mesial and distal surfaces of premolar teeth, with the gingival margin of the cavities 1 mm apical to the CEJ. The samples were randomly assigned to two groups based on the composite resin type and two subgroups based on the light-curing unit type and restored. After 5000 rounds of thermocycling, gingival margin gap in each sample was measured in µm under an electron microscope at ×2000 magnification. Data were analyzed by two-way ANOVA and Tukey tests (α=0.05). Results: Marginal gaps of TNCB composite resin were significantly smaller than those of XTF composite resin (p<0.001). There were no significant differences between the two light-curing units in each group (p=0.887 with XTF and p=0.999 with TNCB). Conclusion: The gaps at gingival margins of Cl II cavities with TNCB bulk-fill composite were smaller than XTF composite resin. Both composite resins can be cured with both the second- and third-generation LEDs.